2020
DOI: 10.1080/16549716.2020.1792192
|View full text |Cite
|
Sign up to set email alerts
|

Exploring national human resource profile and trends of Prosthetists/Orthotists in South Africa from 2002 to 2018

Abstract: Background: The World Health Organization (WHO) in 2017 estimated that around 35-40 million people require prosthetic or orthotic services. The Framework and Strategy for Disability and Rehabilitation 2015-2030 for South Africa highlights a shortage of human resources for disability and rehabilitation services to manage the various risks and types of impairments faced by the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Some authors have revealed that an unequal and imbalanced distribution of prosthetic professionals on whom people rely on is a major issue, particularly in developing countries. 28 Our participants stated similar problems. For example, despite that the prosthesis was expensive, they were able to use it only once before blisters prevented them from using it again.…”
Section: Acceptabilitymentioning
confidence: 73%
“…Some authors have revealed that an unequal and imbalanced distribution of prosthetic professionals on whom people rely on is a major issue, particularly in developing countries. 28 Our participants stated similar problems. For example, despite that the prosthesis was expensive, they were able to use it only once before blisters prevented them from using it again.…”
Section: Acceptabilitymentioning
confidence: 73%
“…This study provides a comprehensive description of the sociodemographic profile and work-related characteristics of the UK PO workforce. While national analyses of the PO workforce were previously conducted in other countries, such as South Africa and Australia, 23,24 this is the first of its kind in the UK.…”
Section: Discussionmentioning
confidence: 99%
“…22 Other countries worldwide have undertaken initiatives to collect information on the number and sociodemographic characteristics of POs. 23,24 However, in the UK, there is currently limited data available regarding the number and sociodemographic characteristics of the PO workforce. In 2017, a report commissioned by Health Education England explored the number of orthotists and dual-practicing POs but lacked data on prosthetists.…”
Section: Introductionmentioning
confidence: 99%
“…De-identified data were collected from the HPCSA database from 2004-2019 using a standardized data collection sheet. A similar approach was adopted as in previous studies [12][13][14][15]. Data included annual volume, province, speciality type as well as the demographic profile by sex, population group and age.…”
Section: Data Collectionmentioning
confidence: 99%